2019
DOI: 10.35631/ijepc.4310015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness on Academic Self-Efficacy: A Randomised Controlled Trial

Abstract: This study examined the effect of a brief mindfulness intervention on academic self-efficacy. Twenty-six university students were randomized to a four-day brief mindfulness intervention or a wait-listed control condition. The brief mindfulness intervention took the form of four 30 minute sessions of mindfulness meditation over four consecutive days. Measures of mindfulness, emotional wellbeing, and academic self-efficacy were obtained via a self-report survey prior to the intervention, post-intervention and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition, we found that social support can also help people get rid of anxiety and depression by actively raising the level of mindfulness. Mindfulness helps them focus on the present and adjust their state to adapt to the current learning and life, promotes students to generate more academic self-efficacy, and improves learning enthusiasm and academic performance [ 57 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that social support can also help people get rid of anxiety and depression by actively raising the level of mindfulness. Mindfulness helps them focus on the present and adjust their state to adapt to the current learning and life, promotes students to generate more academic self-efficacy, and improves learning enthusiasm and academic performance [ 57 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not intended to be exhaustive, but rather to suggest processes that the limited existing literature on acceptance has already shown. Acceptance could first allow access to the feeling of self-efficacy [66] for dealing with the changes that a pregnancy implies. Given the relationship between flexibility and mindfulness for emotion regulation [67], acceptance could further foster flexibility and this would help women to cope with the singular time of the pregnancy and the stressful situation of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The postpartum period appears to be a high-risk time for the development of OCD symptoms [76]. Although the overlap between OCD and depression is still a matter of debate, both in terms of the mechanisms involved and the risk factors [77], obsessive-compulsive personality disorder symptoms could be a risk factor for postpartum depressive symptoms [66][67][68][69][70][71][72][73][74][75][76][77][78]. If additional data reinforce this hypothesis, it suggests that an assessment of OCD or obsessive-compulsive personality disorder may be useful for screening pregnant women for PND risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Xu et al (2022) showed strong evidence that virtual mindfulness therapies can immediately improve academic performance. Menges and Caltabiano (2019), on the other hand, wanted to look into how mindfulness interventions affect academic self-efficacy.…”
Section: Introductionmentioning
confidence: 99%